EVALUATION OF LODGING ESTABLISHMENTS IN CAMPOS USING DEA WITH WEBSITE DATA - Cruz, Nina Amélia Chartuni Cabral da; Raupp, Fernanda Maria Pereira (Pesquisa Operacional para o Desenvolvimento, 2013)
In this work, Data Envelopment Analysis (DEA) technique has been applied to evaluate the efficiency of lodging establishments, in the municipality of Campos dos Goytacazes (Campos in short), RJ, Brazil, from the perspective of the customers, with the intent to support decision making by managers of family-business establishments. Due to the city economic importance, for the evaluation, besides the lodging establishments already installed in Campos, other chain hotels with the potential to be inaugurated in Campos in the very near future are also considered in the analysis. The input and output data for DEA models were collected from the lodging establishment websites. With the efficiency score results obtained with the oriented-output CCR and BCC models, we further indicate the service items that should be improved by the establishments that are considered inefficient. Keywords: lodging establishments, Data Envelopment Analysis, efficiency.